2016
DOI: 10.1155/2016/1769203
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation of Soil Heat Flux at an Antarctic Local Area during Warmer Months

Abstract: Soil heat flux (G) is one term in the energy balance equation, and it can be particularly important in regions with arid, bare, or thinly vegetated soil surfaces. However, in remote areas such as the Antarctic, this measurement is not routinely performed. The analysis of observational data collected by the ETA Project at the Brazilian Antarctic Station from December 2013 to March 2014 showed that, for the total daily energy flux, the surface soil flux heats the deeper soil layers during December and January an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Choi et al [13] reported that the mean monthly net radiation on an ice-free area on King George Island (KGI) was more than two-times larger than the values reported for glaciers in the AP region [9,10,14]. Unlike over ice-covered areas, ice-free ground in high latitudes can also be a heat source for the atmosphere [15]. Furthermore, coastal sites are affected by sea proximity, for instance by increased moisture availability for sublimation when the sea is free of ice [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al [13] reported that the mean monthly net radiation on an ice-free area on King George Island (KGI) was more than two-times larger than the values reported for glaciers in the AP region [9,10,14]. Unlike over ice-covered areas, ice-free ground in high latitudes can also be a heat source for the atmosphere [15]. Furthermore, coastal sites are affected by sea proximity, for instance by increased moisture availability for sublimation when the sea is free of ice [16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, coastal sites are affected by sea proximity, for instance by increased moisture availability for sublimation when the sea is free of ice [16]. However, studies on the surface energy budget in ice-free areas have failed to agree on how the energy is portioned into turbulent and ground heat fluxes [13,15,17], which may be connected to the loss of the low-frequency fluctuation part of fluxes [18]. Thus, further research might help explain the discrepancies.…”
Section: Introductionmentioning
confidence: 99%
“…Another simulation study using desert soils reported that 35% of net solar radiation may be transferred into soils (Niu et al, 1997). Additionally, soil heat flux was found to result in 7.6% of the net radiation being stored within soils during the day, acting as a heat source to the surface soil layers at night, accounting for more than 50% of the net nighttime radiation in the Antarctic during warmer months (Alves and Soares, 2016). Furthermore, long-term temperature monitoring in the Tibetan Plateau , revealed that soil temperatures were generally higher than surface air temperatures (Zhu et al, 2018).…”
Section: The Complementary Roles Of Atmospheric Air and Soil In The Gmentioning
confidence: 99%
“…5b. The soil heat flux is the conduction of energy per unit area in response to a temperature gradient [3]. Shortwave radiation incident on the surface is the most important energy for almost all geophysical processes.…”
Section: Workhop Sobre Areias Monazíticasmentioning
confidence: 99%